Hearing loss and tinnitus in survivors with chemotherapy-induced neuropathy. (February 2018) - Miaskowski, Christine; Paul, Steven M.; Mastick, Judy; Schumacher, Mark; Conley, Yvette P.; Smoot, Betty; Abrams, Gary; Kober, Kord M.; Cheung, Steven; Henderson-Sabes, Jennifer; Chesney, Margaret; Mazor, Melissa; et al.
Abstract: Purpose: The purpose of this study was to evaluate for differences in demographic, clinical, and pain characteristics, as well as measures of sensation, balance, perceived stress, symptom burden, and quality of life (QOL) among survivors who received neurotoxic chemotherapy (CTX) and who reported only chemotherapy-induced neuropathy (CIN, n = 217), CIN and hearing loss (CIN/HL, n = 69), or CIN, hearing loss, and tinnitus (CIN/HL/TIN, n = 85). We hypothesized that as the number of neurotoxicities increased, survivors would have worse outcomes. Methods: Survivors were recruited from throughout the San Francisco Bay area. Survivors completed self-report questionnaires for pain and other symptoms, stress and QOL. Objective measures were assessed at an in person visit. Results: Compared to survivors with only CIN, survivors with all three neurotoxicities were less likely to be female and less likely to report child care responsibilities. In addition, survivors with all three neurtoxicities had higher worst pain scores, greater loss of protective sensation, and worse timed get up and go scores. These survivors reported higher state anxiety and depression and poorer QOL. For some outcomes (e.g., longer duration of CIN, self-reported balance problems), significantly worse outcomes were found for the survivors with CIN/HL and CIN/HL/TIN compared to those with only CIN. Conclusions: Our findings suggest that compared to survivors with only CIN, survivors with CIN/HL/TIN are at increased risk for the most severe symptom burden, significant problems associated with sensory loss and changes in balance, as well as significant decrements in all aspects of QOL. Highlights: Hearing loss and tinnitus warrant assessment in survivors who received neurotoxic chemotherapy. Survivors with CIN, HL, and TIN report a higher symptom burden. Survivors with CIN, HL, and TIN report decrements in function and QOL.